Sistem Pakar Diagnosis Gangguan Obsessive Compulsive Disorder Menggunakan Metode Forward Chaining Berbasis Web - Tri Hastono; Sefti Rohana; Sunggito Oyama (Universitas PGRI Yogyakarta, 2022)
Anxiety disorder is one of the diseases are often encountered in psychology. Anxiety disorders can cause people into try to avoid situations that trigger or worsen their symptoms. There are several types of anxiety disorders, including Obsessive Compulsive Disorder. Obsessive Compulsive Disorder (OCD) is a disorder in witch people have recurring, unwaned thoughts, ideas or sensations (obsessions) that make them feel driven to do something repetitively (compulsions). The repetitive behaviors, such as hand washing and checking the door, can significantly interfere with a person’s daily avtivities and social interactions. Diagnosing what type of obsessive compulsive disorder do people have requires expert especially in psychology. An expert system is a system that requires the knowledge of an expert. This technology will help detecting the tendency of an obsessive compulsive disorder so people can enable to overcome and treat them appropriately. This system implements Forward Chaining to trace the knowledge base, which is consist of the type disorders, symptoms, and the rule. The expert system created by the author is based on a website using the PHP programming language and MySQL database. The output of this program is the name of one of the obsessive compulsive disorder and its solusions. It is hoped the expert system can facilitate and help the public to diagnose obsessive compulsive disorder